(untitled) (Sains Humanika, 2025)
Sexual abuse is a profoundly traumatic experience that can have long-lasting psychological and emotional effects. This case study explores the counseling process with a woman in her 20s (hereafter referred to as Alice) who experienced sexual abuse and struggled with severe social withdrawal. Although the initial presenting issue involved difficulties related to employment, the counsellor’s attitude of valuing what was important to Alice led her to begin discussing her traumatic experiences of sexual abuse. By diving deeper into the recurring theme of frustration within her narrative regarding the sexual abuse, Alice was able to shift her focus towards how that very frustration had acted as an empowering force to better help her in her adversities. This shift in narrative from one of helplessness and avoidance to one of confronting challenges using the power of her frustration resulted in significant behavioral changes, including increased social engagement and motivation to seek employment. Subsequent counselling sessions also revealed that she was not only able to engage in greater self-reflection, but was also able to find the motivation to fill up paper works and secure a job position. In the current study, how the counsellor had focused on Alice’s dominant narrative through the discussions of her traumatic experiences, and how the meaning behind those experiences had transformed for Alice will be examined.